The temporal structure of male`s Olympic boxing matches in flyweight, middleweight and super heavyweight categories: a pilot study - Gutiérrez-Santiago, A.; Vázquez-Estévez, C.; Munoz-Rodrigo, S.; Prieto-Lage, I. (International Journal of Performance Analysis in Sport, 2023)
The objective of this research was to define the temporal structure of Olympic boxing in males in the flyweight, middleweight and super heavyweight categories. The participants were boxers of the stated categories, who competed in the Tokyo 2020 Olympic Games. Using observational methodology, we analysed all the matches in these categories from the round of 16 (n = 45). To obtain the results, we used different analysis techniques with SPSS: descriptive analysis, Shapiro-Wilk, one-factor ANOVA, Kruskal-Wallis test and chi-square. The significance level used was p < 0.05. The results define the time structure models for each of the weight categories in the three rounds of combat. With these models, coaches and sport technicians will be able to establish the optimal training loads for their athletes. We found significant differences in the total number of punches and in the ring area where the punches were made, resulting in the flyweight category being where most actions are taken in both cases. In the three weight categories, the differences among the three rounds are minimal. We conclude that most of the combats end in the third round, consuming the total fighting time in the three weight categories.